The quality of life among the elderly people in Sarawak - Cosmas, Felicia; Aren, Merikan (Universitas Negeri Padang, 2019)
Changes in physical, psychological, hormonal and the social conditions occurred in the process of ageing. These changes are expected to bringing impact to the quality of life of the elderly people. The aim of the study is to assess the quality of life and its related factors among the elderly population in Sarawak. A quantitative research has been conducted in the form of survey research by distributing WHOQOL-BREF questionnaire. The study was conducted among the elderly people aged 60 years and above who are living in Sarawak. The sample size of the study was 130 participants that were obtained through snowballing sampling. The data were analysed using Pearson Correlation which was to find out the relationship between each domain and the quality of life of the elderly people in Sarawak. The results obtained shows that the mean score of WHOQOL-BREF was 90.17 whereby the mean scores of the domain environment score the highest among the four domains. In conclusion, the overall score of the quality of life of the elderly people in Sarawak was average.